The past and present of the nurse role in the act of care - Dandicourt Thomas, Caridad (2017)
INTRODUCTION: The practice of care has existed since time began. Its origin is related to the necessity of survival in which was developed life of the first humans, also it’s related to maternal interventions that assured the life and specie continuity. MATERIALS AND METHODS: Through the technique of bibliographical review, it was made an exhaustive analysis of the selected sample that involves, as whole, the historical evolution of people, families, communities (including its groups) health care. DEVELOPMENT: According to Francoise Colliere, french theorist, take care means “to move human abilities of the human being in sickness or health state, considering its customs, to accomplish the growth and development from birth until death. It also demands the caregiver to develop many abilities of perception, comprehension, just like ingenuity, inventiveness and creativity.” According to the authors, this definition shows care as a social process, whose objective goes beyond sickness. For this, it’s required abilities, knowledge and skills. CONCLUSIONS: The evolution from trade to profession, from profession to discipline, and from scientific discipline to science and art implies a historical process of rationalization and consciousness of its social role about caring people, families, groups, community, and society.